Predictive Value of Sudden Olfactory Loss in the Diagnosis of COVID-19 - Haehner, Antje (ORL J Otorhinolaryngol Relat Spec, 2020)
INTRODUCTION: Recent reports suggest that sudden smell loss might be a symptom of SARS-CoV-2 infection. The aim of this study was to investigate the frequency of olfactory loss in an outpatient population who presented to a coronavirus testing center during a 2-week period and to evaluate the diagnostic value of the symptom “sudden smell loss” for screening procedures. METHODS: In this cross-sectional controlled cohort study, 500 patients who presented with symptoms of a common cold to a corona testing center and fulfilled corona testing criteria completed a standardized diagnostic questionnaire which included the patients' main symptoms, time course, and an additional self-assessment of the patients' current smell, taste function, and nasal breathing compared to the level before the onset of symptoms. RESULTS: Out of the 500 patients, 69 presented with olfactory loss. Twenty-two of them subsequently tested positive for SARS-CoV-2. Only 12 out of the patients without olfactory loss tested positive, resulting in a frequency of 64.7% for the symptom “sudden smell loss” in COVID-19 patients. Compared to COVID-19 patients without smell loss, they were significantly younger and less severely affected. Changes in nasal airflow were significantly more pronounced in SARS-CoV-2 negative patients with olfactory complaints compared to the patients with smell loss who tested positive for SARS-CoV-2. By excluding patients with a blocked nose, the symptom “sudden smell loss” can be attested a high specificity (97%) and a sensitivity of 65% with a positive predictive value of 63% and negative predictive value of 97% for COVID-19. CONCLUSION: Considering the high frequency of smell loss in non-hospitalized COVID-19 patients, acute olfactory impairment should be recognized as an early symptom of the disease and should be tested for on a regular basis. In contrast to other acute viral smell impairment, COVID-19-associated smell loss seems to be only rarely accompanied by a severely blocked nose.